Afektivno vezivanje i emocionalna regulacija kod adolescenata sa depresijom - Kosutic, Zeljka; mitkovic voncina, marija; dukanac, vesna; lazarevic, milica; rakovic dobroslavic, ivana; soljaga, mina; peulic, aleksandar; duric, mina; pesic, danilo; bradic, zagorka; Lecic tosevski, Dusica (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Attachment and emotion regulation skills are recognized as important factors in the development of depression, but their specifics have rarely been discussed in clinical adolescent population. The aim of our study was to investigate attachment and emotion regulation strategies in adolescents with depression. Methods. The sample consisted of 101 adolescents, age 16 to 24, divided into three groups: 1) 41 adolescents with the diagnosis of depressive disorder; 2) 30 adolescents with the diagnosis of anxiety disorder; 3) 30 health adolescents (without psychiatric diagnosis). The assessment was done by the following instruments: the Socio-demographic questionnaire; the Semistructured clinical interview (SCID-I) for the Diagnostic and Stratistical Manual of Mental Disorders, Fourth Edition (DSM-IV); the Beck Depression Inventory (BDI); the Inventory of Parent and Peer Attachment (IPPA) and Emotional Regulation Questionnaire (ERQ). Data were analyzed using MANCOVA and partial correlation, with gender, age and birth order as covariates. Results. The adolescents with depressive disorders had less secure attachment to mother and peers than the health adolescents and less secure attachment to father comparing to other two groups (MANCOVA F = 4.571; p = 0.000). The adolescents with anxiety disorder had less secure attachment to father and peers compared to the healthy adolescents group (p
Keywords: adolescent; depression; emotions; object attachment